Prarancangan Pabrik Bisphenol-A dari Phenol dan Aceton Kapasitas 25.000 Ton/Tahun - RAMADHAN, Prarizka Listyanto, Kusmiyati, S.T, M.T, Ph.D, Ir.Herry Purnama, M.T., Ph.D (2015)
In the era of technological advances in various fields of development was rapid, it would require some sort of infrastructure for the era of free competition. One of the prospects for future development is to build a factory that has competitiveness with foreign products. One of them is by establishing Bisphenol-A plant with raw materials Phenol and Aceton. with a capacity of 25,000 tons per year is planned to operate for 330 days per year. Acetone-making process is done in RATB reactor (CSTR). In the reactor the reaction at liquid-liquid phase, irreversible, exothermic, non-adiabatic, isothermal at the feed temperature of 50 ° C and a pressure of 1 atm. The factory is classified as low-risk plant operating conditions at atmospheric pressure. Phenol for this plant needs as much 2617.2983 kg per hour and needs as much Aceton 807.0363 kg per hour. Bisphenol-A products such as 3151.8308 kg per hour, and the water as much as 4.7349 kg per hour. Process support utilities includes water supply of 60,000 kg per hour were obtained from river water, the provision of 5784.8235 kg of saturated steam per hour compressed air requirement of 150 m3 per hour, the demand for electricity is obtained from the PLN and two generator sets of 400 kW as reserves, as much as 3.0034 liter of fuel per hour. The factory was established in Cilegon industrial area with a land area of ​​30,000 m2 and the number of employees 145 people. Bisphenol-A factory uses a fixed capital of USD 273 988 475 856 and working capital of Rp 125,813,192,263. From the economic analysis of this plant show a profit before tax of USD 121 074 731 088 per year after taxes 30% profit reached Rp 36,322,419,326 per year. Percent Return On Investment (ROI) before taxes 44.190% and 30.933% after tax. Pay Out Time (POT) before taxes for 1,845 years and 2,443 years after tax. Break Even Point (BEP) of 44.562%, and Shut Down Point (SDP) of 28.387%. From the data above feasibility analysis concluded that the plant is profitable and feasible to be established.